A. Shah (2018). Nightmarch. Among India’s revolutionary guerrillas. Londres: Hurst. 256 pp. - Vázquez León, Luis (Estudios de Asia y África, 2019)
A. Shah (2018). Nightmarch. Among India’s revolutionary guerrillas. Londres: Hurst. 256 pp.